Asuhan Kebidanan Continuity of Care (COC) pada Ny ‘N’ Usia 38 Tahun di Klinik Aria Medistra Kabupaten Semarang - Diah Ari Murti Afsari; Rini Susanti (Universitas Ngudi Waluyo, 2025)
Based on the digital recording system of Maternal Perinatal Death Notification data, Central Java is included in the 3 provinces with the highest MMR. Therefore, innovation and acceleration strategies are needed to achieve the expected target. The purpose of this case study is to provide comprehensive midwifery care to Mrs. 'N' who is 38 years old. Care is provided with a continuity of care approach according to midwifery service standards starting from pregnancy, childbirth, postpartum period, BBL care, to family planning services. The care method applied is descriptive, with a Case study approach. The implementation of care was carried out during the period from November 2024 to April 2025. Data collection techniques include primary and secondary data. Primary data was collected through physical and supporting examinations, interviews, and direct observation while secondary data was from the maternal and child health book (KIA). During pregnancy, Mrs.